Thyroglossal Duct Cysts and Fistulas: A Review of 32 Cases - Alpay, Hayrettin Cengiz; Kaygusuz, İrfan; Karlıdağ, Turgut; Keleş, Erol; Yalçın, Şinasi; Dabak, Hakan (Fırat University, 2007)
Objectives: To present our experiences in management of thyroglossal duct cysts over 10 years and to discuss the diagnosis and treatment of thyroglossal duct cysts related with literature. Materials and Methods: A retrospective review of charts belonged to 32 patients performed excision of thyroglossal duct cysts in our clinic. Results: 12 of the 32 patients were male and 20 were female. The age at presentation ranged from 2 to 56 years (average age 17.9±16.1 years). The most common complaint was intermittent secretion at the middle region of the neck (53%). Rarely, a nodule or fistula point was being at the middle of the neck in patients. Fistula point or nodule was settled at the midline of the neck and thyrohyoid zone in 16 patients. Clinic presentation was a fistula in 17 patients and a cyst in 15 patients. Sistrunk operation was performed for all our patients. Conclusion: Common opinion accepted about the treatment of thyroglossal duct cysts is surgical approach. It should be remembered that the thyroglossal duct cysts have risk of malign transformation. Physicians must keep in mind the thyroglossal duct cysts in the differantial diagnosis of the patients presented with fistula or nodule at middle of the neck and the sistrunk operation is a gold standart for the treatment of this patients. ©2007, Fırat Üniversity, Medical Faculty

Giriş: On yıllık bir periyottaki tiroglossal duktus kisti tedavisindeki tecrübelerimizi sunmak, tiroglossal duktus kistlerinin tanı ve tedavisini ilgili literatür ışığında tartışmaktır. Gereç ve Yöntem: Kliniğimizde tiroglossal duktus kisti tanısı alan ve tedavi edilen 32 vakanın dosyası retrospektif olarak yeniden incelendi. Bulgular: 32 hastanın 12'si erkek, 20'si bayandı ve yaşları 2 ile 56 arasında (ortalama 17.9±16.1 yıl) değişiyordu. En sık rastlanan şikayeti boyun orta hattında aralıklı akıntıydı (%53). Daha nadir olarak hastalarda boyun orta hattında şişlik veya fistül ağzı şikayeti vardı. 16 hastada fistül ağzı veya şişlik boyun orta hattında ve tirohiyoid bölgedeydi. Klinik görünüm 17 hastada fistül ve 15 hastada kist şeklindeydi. Hastalarımızın tümüne Sistrunk operasyonu uygulandı. Sonuç: Tiroglossal duktus kistlerinin genel olarak kabul görmüş tedavisi cerrahidir. Bu kistlerin malign transformasyon riskinin olduğu bilinmelidir. Boyun orta hattında şişlik veya kitle ile gelen hastaların ayırıcı tanısında tiroglossal duktus kistleri de akla gelmeli ve tedavisinde sistrunk ameliyatının altın standart olduğu unutulmamalıdır. ©2007, Fırat Üniversitesi, Tıp Fakültesi
Tiroglossal Duktus Kist ve Fistülleri: 32 Vakalık Bir İnceleme